Potehi Puppet (布袋戲) in Java - Hirwan Kuardhani (Dance and Theatre Review, 2018)
AbstractPotehi (布袋戏) puppet theater in Java is called as Chinese puppet and originated from Fujian (福建) and Guangdong (广东) Province. Chinese puppets that were allegedly meant here is Potehi because the forms of other kinds of puppet theater from China was not discovered the traces. Leather puppet, such as Purwa, or string puppet (marionette), or even Rod puppet is not recognized by the Javanese people, most of them are only familiar with Potehi Chinese puppet. This is confirmed by the data that most Chinese emigrants who came to Java is the Hokkien (Fujian) who owned Potehi puppet theater. Some of Potehi playhouse stage are in the form of permanent building of a brick wall that has been decorated with images of deities or knock -down building which is similar to ronda substations that can be assembled. When Potehi stage is used for shows in pagoda, it will be included in the playhouse stage. It is different if the shows take place outside the pagoda, such as in malls, galleries, churches, festivals and so on, then it will be without the playhouse stage. Potehi stage shaped like a castle building with division of imaginary spaces. The upper part is the sky or deities’ palace, and the bottom is the human castle. It can also be interpreted as two natures; macrocosm and microcosm. The Sky Palace keep supervising the administration of human castles that have been mandated to regulate human. General grip of Potehi Puppet Theatre in Java includes: material story and a common way of presenting the general grip of the story of Potehi Puppet Theatre in Java that include: materials and way of presenting sequence actions stories that are taken by sehu and the board of pagoda when holding Potehi show in pagoda are as follow: 1 Sehu prepares the figures. 2. Sehu with Lauw Cu (the board of pagoda) perform Puak Poe rituals. 3. Sehu prepare the staging equipment. 4. The show is based on the agreed time with pagoda sides. Potehi shows for the Chinese community carry out ritual, social, and educational functions.Keywords: puppet theater; Potehi; Javanese performanceAbstrakWayang Potehi di Jawa. Teater Boneka Potehi di Jawa disebut sebagai pertunjukan boneka Cina yang berasal dari Provinsi Fujian dan Guandong. Diduga pertunjukan Potehi datang ke Pulau Jawa pada abad ke-16. Wayang Potehi dikenal sebagai wayang Cina karena bentuknya tidak ditemukan di wilayah Jawa. Wayang kulit di Jawa sama dengan wayang Purwa, wayang bertangkai di Jawa dikenal dengan wayang golek. Teater boneka Potehi dibawa para emigran Hokkian (Fujian) ke Jawa, dan dimainkan pada panggung permanen ataupun panggung yang berpindah. Ketika pertunjukan Potehi dimainkan di Kelenteng, digunakan stage yang permanen berbentuk rumah-rumahan. Hal demikian berbeda dengan pertunjukan yang dimainkan di luar Kelenteng, seperti di mal, galeri seni, gereja, atau festival-festival. Panggung Potehimerupakan perwujudan simbol dunia, yakni paling atas adalah istana langit yangmerupakan tempat para dewa, sementara bagian bawah adalah istana manusiabiasa atau tempat masyarakat biasa. Hal tersebut dapat digambarkan sebagaialam makrokosmos dan alam mikrokosmos. Secara keseluruhan, pementasanPotehi di Jawa masih mengikuti patokan, lakon, tatacara Potehi asalnya, yaitu:1. Sehu atau dalang menyiapkan lakon dan mengajukan judul lakon yang akandibawakan. 2. Sehu bersama Lauw Cu (petugas upacara) melakukan ritual PuakPoe. 3. Sehu mendapatkan persetujuan mengenai lakon yang akan dibawakan. 4. Pertunjukan digelar berdasarkan lakon yang telah disetujui dewa. PertunjukanPotehi bagi komunitas masyarakat Tionghoa membawa serta fungsi sosial, ritual,dan pendidikan.Kata kunci: teater boneka; Potehi; pertunjukan Jawa